기관근의 수축성에 대한 말초성 Benzodiazepine수용체의 역할 - 류한영(Han Young Rhyu); 최형철(Hyung Cheol Choi); 최은미(Eun Mee Choi); 손의동(Uy Dong Sohn); 이광윤(Kwang Youn Lee); 김원 (The Korean journal of physiology & pharmacology, 1997)
Non-neuronal high affinity binding sites for benzodiazepines have been found in many peripheral tissues including cardiac muscle and vascular smooth muscle, and have been designated as 'peripheral benzodiazepine receptor'. Benzodiazepines have been shown to induce relaxation of the ileal, vesical, and uterine smooth muscles. However, it is still unclear about possible involvement of peripheral benzodiazepine receptor on the contractility of trachealis muscle. This study was performed to investigate the role of the peripheral benzodiazepine receptor on the contractility of canine trachealis muscle. Canine trachealis muscle strips of 15 mm long were suspended in an isolated organ bath containing 1 ml of physiological salt solution maintained at $37^{°}C$, and aerated with $95%\;O_2/5%\;CO_2$. Isometric myography was performed, and the results of the experiments were as follows: Ro5-4684, FGIN-1-27 and clonazepam reduced a basal tone of isolated canine trachealis muscle strip concentration dependently, relaxant actions of RoS-4684 and FGIN-1-27 were antagonized by PK11195, a peripheral benzodiazepine receptor antagonist. Flumazenil, a central type antagonist, did not antagonize the relaxant action of Peripheral type agonists. Saturation binding assay of [3H]Ro5-4864 showed a high affinity$(Kd=5.33{±}1.27nM,\;Bmax=\;867.3{±}147.2\;fmol/mg\;protein)$ binding site on the canine trachealis muscle. Ro 5-4684 suppressed the bethanechol-, 5-hydroxyoyptamine- and histamine- induced contractions. Platelet activating factor (PAF) exerted strong and prolonged contraction in trachealis muscle strip. Strong tonic contraction by PAE was attenuated by Ro 5-4684, but not by WEB 2086, a PAF antagonist. Based on these results, it is concluded that the peripheral benzodiazepine receptor mediates the inhibitory regulation of contractilty of canine trachealis muscle.